Development Of Texture Modified Pumpkin Porridge For Dysphagia Diet: The Effects Of Fish Gelatin-Microbial Transglutaminase Gel Microparticles On The Rheological And Sensory Characteristics - Rosly, Siti Munirah (2024)
Dysphagia is a condition affecting people of all ages, particularly the elderly and those with diseases like cancer, stroke, and dementia. It can reduce food intake and lead to nutritional deficiencies. To manage dysphagia, texture-modified food is prepared using thickeners like starch and gum, but these can leave a strong aftertaste or cause stomach discomfort. Therefore, in phase 1 of this study, gel microparticles were developed from fish gelatin and microbial transglutaminase enzyme (tga) as a potential thickener for texture-modified foods. The gel microparticles, ranging from 18μm to 1445μm, showed safe swallowing bolus properties with low adhesiveness and high cohesiveness, demonstrating the potential of gel microparticles with 0.7% mtga as a suitable thickener for texture modification. The rheological analysis showed that the sample with 0.7% mtga has weak gel properties with more elastic behaviour than viscous behaviour. In addition, sugar concentration increases hardness and cohesiveness while decreasing adhesiveness, making it as easy-to-swallow foods. In phase 2, the effects of gel microparticles on pumpkin porridge’s texture, rheological properties, and amylase enzyme response were analysed. The use of 2% fish gelatin-microbial transglutaminase (fgmt) gel microparticles showed similar texture, viscosity, and flow behaviour to the samples added with commercial thickeners. The elasticity of the porridge was dominant, with a higher resistance to the amylase reaction, indicating safe swallowing properties.